Role of Glial Cells in μ-Opioid Receptor-Mediated Vasodilation in the Rat Retina. (4th March 2018) - Someya, Eriko; Mori, Asami; Asano, Daiki; Morita, Akane; Sakamoto, Kenji; Nakahara, Tsutomu
ABSTRACT: Purpose : Our recent study demonstrated that herkinorin, a non-opioid μ-receptor agonist derived from salvinorin A, dilates retinal arterioles through stimulation of μ-opioid receptors in rats. Activation of neuronal nitric oxide (NO) synthase and the presence of ganglion cells in the retina appear to be crucial for inducing μ-opioid receptor-mediated retinal vasodilation. In the present study, we examined the role of the interaction between neurons and glia in the retinal vasodilator mechanism involving μ-opioid receptors in rats. Materials and methods : The localization of μ-opioid receptors and neuronal NO synthase (nNOS) in the rat retina was examined using immunohistochemistry. The retinal vascular responses were evaluated by measuring the diameter of retinal arterioles in in vivo fundus images. Both systemic blood pressure and heart rate were continuously recorded. Results : Immunoreactivity of μ-opioid receptors was found in ganglion cells and astrocytes, while that of nNOS was detected in ganglion cells and amacrine cells. Herkinorin increased retinal arteriolar diameter without significantly changing mean blood pressure and heart rate. The retinal vasodilator response to herkinorin was significantly attenuated by treatment with glial toxins (fluorocitrate and disialoganglioside-GD1b). The glial toxins markedly prevented vasodilation induced by intravitreal injection, but not by intravenous infusion, of NOR3, an NO donor. Conclusion : These results suggest that retinal glial cells play an important role in the μ-opioid receptor-mediated retinal vasodilation in rats. Stimulation of μ-opioid receptors on retinal ganglion cells may affect the activity of glial cells, thereby changing retinal vascular tone.